2018
DOI: 10.2134/cftm2018.02.0006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pyraclostrobin Foliar Fungicide, Corn Hybrid, and Harvest Timing on Stalk Health of Corn

Abstract: Core Ideas A foliar fungicide applied at the corn tasseling stage can reduce stalk rot severity but is likely related to control of foliar diseases. If corn harvest is delayed, stalk rot severity can increase. Corn hybrids with resistance to gray leaf spot may have reduced stalk rot compared with susceptible hybrids. The use of foliar‐applied fungicides on corn (Zea mays) in the United States has been heralded as a way to improve stalk health. Our goal was to provide evidence whether the use of pyraclostrobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Late-season foliar disease development occurring closer to the rating date (dough through dent (R4-R5)) would have less impact on grain fill and yield response but still result in high foliar disease severity values. Furthermore, other studies that have examined the impact of VT applications of foliar fungicides have observed non-significant effects on yield when significant reductions of foliar disease were observed at greater than 5% severity in the non-treated control [9, 2427]. Yield increases from VT fungicide applications also have been observed under low disease pressure in other studies [7, 26], and are attributed to the control of lesser foliar diseases and physiological effects caused by fungicides, such as delayed senescence [28].…”
Section: Discussionmentioning
confidence: 99%
“…Late-season foliar disease development occurring closer to the rating date (dough through dent (R4-R5)) would have less impact on grain fill and yield response but still result in high foliar disease severity values. Furthermore, other studies that have examined the impact of VT applications of foliar fungicides have observed non-significant effects on yield when significant reductions of foliar disease were observed at greater than 5% severity in the non-treated control [9, 2427]. Yield increases from VT fungicide applications also have been observed under low disease pressure in other studies [7, 26], and are attributed to the control of lesser foliar diseases and physiological effects caused by fungicides, such as delayed senescence [28].…”
Section: Discussionmentioning
confidence: 99%
“…Fungicide use may be a consideration to minimize stalk rot and preserve stalk quality during harvest, though stalk rot will still increase if harvest is delayed appreciably (Shelby et al, 2018). Growers can minimize yield and quality losses associated with stalk lodging by harvesting fields with stalk Crop Science rot as early as possible (Paul & Thomison, 2019).…”
Section: Management Response and Recommendationsmentioning
confidence: 99%
“…Corn lodging is usually caused by excessive planting density, improper use of fertilizer, unreasonable irrigation or diseases, and pests during the growth period ( Echezona, 2007 ; Shelby et al, 2018 ; Liu et al, 2021 ). The bending strength and rind puncture resistance of stalks are usually taken as the indices for lodging resistance in variety breeding ( Albrecht et al, 1986 ; Robertson et al, 2016 ; Seegmiller et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%